Pendampingan Rebranding Logo dan Card Olshop dalam Meningkatkan Brand Awareness UMKM Basreng Bojot di Rungkut, Waru, Sidoarjo - Mufaizah, Mufaizah; Salsabilla, Amalia (Universitas Pahlawan Tuanku Tambusai, 2025)
MSMEs play a strategic role in the national economy, but amid the development of the digital era and the rise of online shops, many MSMEs have not optimally utilized visual branding strategies. This study aims to improve the competitiveness of MSMEs through community service activities in the form of logo rebranding assistance and online shop card creation for Basreng Bojot MSMEs. The method used is qualitative descriptive with a participatory approach, encompassing assessment, implementation, and post-activity evaluation stages. The results of the activity indicate that the updated logo, which is more representative, and the addition of an online shop card containing contact information and social media links have successfully enhanced the visual appeal of the products, strengthened the brand image, and facilitated interaction with consumers. Positive feedback from consumers and increased understanding among SME operators regarding design and branding indicate that rebranding has a significant impact on business development. This activity contributes to strengthening visual branding literacy among SME operators and serves as a reference for creativity-based marketing strategies in the digital era.